The Influence of Iconnet Product Personal Selling on the Purchase Interest of Housing Residents in Medan City - Maria Bona Putri S; Ratih Hasanah Sudradjat (Publikasi Indonesia, 2024)
This study aims to analyze the influence of ICONNET product personal selling on the purchase interest of housing residents in Medan City. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 150 respondents who are housing residents in Medan City. Data analysis was conducted using simple linear regression to test the influence of personal selling on purchase interest. The results of the study indicate that personal selling has a positive and significant influence on the purchase interest of housing residents. Effective personal selling increases consumer purchase interest in ICONNET products. These findings have implications for marketing management that personal selling strategies can be an effective tool to boost sales, particularly in the telecommunications industry in residential areas. Recommendations for future research include adding other variables such as product quality and price to see their effects on purchase interest more comprehensively.